2020
DOI: 10.25110/arqsaude.v24i3.2020.7875
|View full text |Cite
|
Sign up to set email alerts
|

Maslach Burnout Inventory - Human Services Survey (Mbi-Hss): Revisão Integrativa De Sua Utilização Em Pesquisas Brasileiras

Abstract: O objetivo desta revisão integrativa é analisar a utilização do Maslach Burnout Inventory - Human Services Survey (MBI-HSS) em pesquisas brasileiras sobre a Síndrome de Burnout em profissionais de saúde. Foi realizada, em maio de 2019, busca sistemática nas bases de dados BVS Enfermagem, Index Psicologia, LILACS, MedLine e na SciELO com a combinação dos descritores “esgotamento profissional”, “pessoal de saúde” e “Síndrome de Burnout” no título, resumo e assunto dos artigos. Buscaram-se textos em inglês, portu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
0
3
0
5
Order By: Relevance
“…The evidence of the aforementioned factors in public health services should be considered and will help us in terms of understanding that the development of burnout syndrome in health care professionals may be related to the organization and development of the work process in these services, which reflects the importance of conducting this study in the current context. Considering the global importance of MBI for identifying burnout syndrome [ 38 ], we conducted a preliminary search in the Joanna Briggs Institute (JBI) evidence synthesis, the international Prospective Register of Systematic Reviews (PROSPERO), Cochrane Library, and PubMed/MEDLINE databases by using the descriptors “health care professionals,” “public health services,” “Maslach Burnout Inventory,” and “burnout syndrome.” We found only 1 integrative review synthesizing the use of MBI in Brazil; however, this study was not directed to public health care professionals [ 39 ]. No studies or protocols were found when expanding the search to other continents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence of the aforementioned factors in public health services should be considered and will help us in terms of understanding that the development of burnout syndrome in health care professionals may be related to the organization and development of the work process in these services, which reflects the importance of conducting this study in the current context. Considering the global importance of MBI for identifying burnout syndrome [ 38 ], we conducted a preliminary search in the Joanna Briggs Institute (JBI) evidence synthesis, the international Prospective Register of Systematic Reviews (PROSPERO), Cochrane Library, and PubMed/MEDLINE databases by using the descriptors “health care professionals,” “public health services,” “Maslach Burnout Inventory,” and “burnout syndrome.” We found only 1 integrative review synthesizing the use of MBI in Brazil; however, this study was not directed to public health care professionals [ 39 ]. No studies or protocols were found when expanding the search to other continents.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the global importance of MBI for identifying burnout syndrome [38], we conducted a preliminary search in the Joanna Briggs Institute (JBI) evidence synthesis, the international Prospective Register of Systematic Reviews (PROSPERO), Cochrane Library, and PubMed/MEDLINE databases by using the descriptors "health care professionals," "public health services," "Maslach Burnout Inventory," and "burnout syndrome." We found only 1 integrative review synthesizing the use of MBI in Brazil; however, this study was not directed to public health care professionals [39]. No studies or protocols were found when expanding the search to other continents.…”
Section: Introductionmentioning
confidence: 99%
“…Apenas 1,8% dos participantes apresenta sentimentos compatíveis com despersonalização, 18,8% apresenta sentimentos face à RP predisponentes para o Burnout, sendo que 21,4% apresenta sentimentos de exaustão emocional associados ao Burnout. Os níveis de coping apresentados perante a pandemia COVID-19 são baixos (47%) para a maior parte dos participantes, seguindo-se os níveis moderados (29,8%), 28 , sendo os pontos de corte usados nos estudos divergentes entre si, dificultando a sua comparabilidade e validade externa 28 . No entanto, a leitura dos resultados da MBI-HSS é complexa e carece de pontos de referência que permitam comparações entre classificações.…”
Section: Resultsunclassified
“…A heterogeneidade na taxa de prevalência da SB entre os diversos estudos é esperada e se deve, em parte, à falta de consenso na interpretação dos instrumentos de identificação dessa condição (38) .…”
Section: Análiseunclassified
“…Parece haver uma associação entre a intolerância à ambiguidade, ou seja, a capacidade de tolerar a falta de informações confiáveis, credíveis ou adequadas, e a redução do bem-estar psicológico em estudantes de medicina e médicos. Culturas e ambientes de trabalho podem ser projetados para reduzir a probabilidade de que a intolerância de um indivíduo à ambiguidade progrida para problemas com seu bem-estar psicológico, como aumentar a provisão de supervisão (38)(39) .…”
Section: Análiseunclassified